Respuestas
Respuesta dada por:
27
Primero debemos de escribir la fórmula para calcular
y es la siguiente:
![a_{n}=a_{1}*r^{n-1} \\ a_{n}=a_{1}*r^{n-1} \\](https://tex.z-dn.net/?f=a_%7Bn%7D%3Da_%7B1%7D%2Ar%5E%7Bn-1%7D++%5C%5C)
Como conocemos
podemos despejar
:
![r^{n-1}= \frac{a_{n}}{a_{1}} \\
r = \sqrt[n-1]{\frac{a_{n}}{a_{1}}} \\
r^{n-1}= \frac{a_{n}}{a_{1}} \\
r = \sqrt[n-1]{\frac{a_{n}}{a_{1}}} \\](https://tex.z-dn.net/?f=+r%5E%7Bn-1%7D%3D+%5Cfrac%7Ba_%7Bn%7D%7D%7Ba_%7B1%7D%7D+%5C%5C%0Ar+%3D++%5Csqrt%5Bn-1%5D%7B%5Cfrac%7Ba_%7Bn%7D%7D%7Ba_%7B1%7D%7D%7D+%5C%5C%0A+++)
Sustituimos los valores:
![r = \sqrt[4]{\frac{2500}{4}} \\
r= \sqrt[4]{625} \\
r= 5 r = \sqrt[4]{\frac{2500}{4}} \\
r= \sqrt[4]{625} \\
r= 5](https://tex.z-dn.net/?f=r+%3D++%5Csqrt%5B4%5D%7B%5Cfrac%7B2500%7D%7B4%7D%7D+%5C%5C%0Ar%3D++%5Csqrt%5B4%5D%7B625%7D+%5C%5C%0Ar%3D+5++)
Como conocemos
Sustituimos los valores:
Preguntas similares
hace 7 años
hace 7 años
hace 7 años
hace 9 años
hace 9 años